Implementation of Energy Dispersive X-ray Fluorescence (EDXRF): Its Principle, Advantages, and Drawbacks - Taiwo Bukola Fasiku; Taiwo Victoria Oluwasusi (Darul Yasin Al Sys, 2025)
Energy Dispersive X-ray Fluorescence (EDXRF) is a widely used technique for the chemical characterisation of materials in different forms, including powders, liquids, and gases, owing to its rapid and non-destructive determination of elemental composition. This review aims to describe the underlying principle of EDXRF and to synthesise its applications, advantages, and limitations across various domains. Drawing on reported uses of EDXRF in archaeology, metallurgy, environmental science, and the food and pharmaceutical industries, the study highlights how both portable and desktop instruments have enabled efficient routine analysis and quality control. In particular, EDXRF has been instrumental in identifying gaps in production processes, especially in food and drug quality control, which in some cases, has led to the withdrawal of non-compliant products from the distribution chain. At the same time, the review underscores key limitations observed in practice, including poor detection of light elements, the impact of moisture, high background noise, spectral interference, and particle-size effects. EDXRF nonetheless offers important advantages such as minimal sample preparation, non-destructive analysis, cost-effectiveness, and operational simplicity. The review concludes that, despite these limitations, EDXRF remains a powerful tool for multi-sectoral chemical characterisation and quality control, and it recommends further development of monochromatic EDXRF configurations to reduce spectral interference, improve detection limits, and enhance analytical accuracy, thereby strengthening its role in regulatory and industrial applications.